Training To Recycle Organic Waste Into Compost - Muhammad Farly Rizky; Wahyu Eko Pujianto (Pengabdian: Jurnal Abdimas, 2024)
ABSTRAK This Community Service Program (PPM) can help people who still leave or throw away a lot of rubbish, of course organic waste, to better utilize and manage the remaining waste potential for now. Organic waste itself means materials that are discarded or destroyed from sources of human activity or natural processes, which do not yet have economic value and whose existence is no longer needed or utilized by humans. This activity aims to provide training to overcome the problem of organic waste produced in the environment and provide knowledge and skills to the community to process organic waste which is useful and valuable by making compost from organic waste.